2016
DOI: 10.1002/2016pa002950
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the depth habitat of the Oligocene planktic foraminifera (Dentoglobigerina venezuelana) induced by thermocline deepening in the eastern equatorial Pacific

Abstract: Understanding planktic foraminiferal depth habitat along with consistent taxonomic concepts is key to accurate reconstruction of paleoceanographic records. The Oligocene‐Pliocene long‐ranging and widely distributed species Dentoglobigerina venezuelana lived in the mixed layer (shallower) during the early Oligocene, whereas the same species calcified at thermocline or subthermocline depths (deeper) during the late Oligocene and Miocene. The exact timing of the species' depth habitat change and its possible rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
(174 reference statements)
2
16
0
Order By: Relevance
“…We therefore speculate that a localised, temporary expansion of the oxygen minimum zone may have led to this peak in abundance in C9n. The enhanced abundance is coincidental with a period of gigantism in Paragloborotalia opima (Wade et al 2016) and the migration to deeper depths observed in Dentoglobigerina venezuelana at Site U1334 (Matsui et al 2016) and Site 1218 ; Supplementary Fig. S1), which Matsui et al (2016) suggested was coincidental with a deepening of the thermocline.…”
Section: Controls On the Abundance Of Chiloguembelina Cubensis At Sitmentioning
confidence: 72%
See 1 more Smart Citation
“…We therefore speculate that a localised, temporary expansion of the oxygen minimum zone may have led to this peak in abundance in C9n. The enhanced abundance is coincidental with a period of gigantism in Paragloborotalia opima (Wade et al 2016) and the migration to deeper depths observed in Dentoglobigerina venezuelana at Site U1334 (Matsui et al 2016) and Site 1218 ; Supplementary Fig. S1), which Matsui et al (2016) suggested was coincidental with a deepening of the thermocline.…”
Section: Controls On the Abundance Of Chiloguembelina Cubensis At Sitmentioning
confidence: 72%
“…The enhanced abundance is coincidental with a period of gigantism in Paragloborotalia opima (Wade et al 2016) and the migration to deeper depths observed in Dentoglobigerina venezuelana at Site U1334 (Matsui et al 2016) and Site 1218 ; Supplementary Fig. S1), which Matsui et al (2016) suggested was coincidental with a deepening of the thermocline. The synchronicity of the peak in C. cubensis, gigantism in P. opima and depth migration of D. vene zuelana suggests that these events may have been driven by complex changes in oceano -graphy, at least on a localised scale through Chron C9n at Site U1334.…”
Section: Controls On the Abundance Of Chiloguembelina Cubensis At Sitmentioning
confidence: 72%
“…Although the δ 13 C values of P. siakensis and D. venezuelana were very similar, slightly higher values of the former species than the latter from 15.9 to 14.6 Ma and from 13.4 to 12.4 Ma (Figure ) still support a shallower habitat of P. siakensis . A previous habitat depth assignment has also reported a mixed‐layer habitat for P. siakensis (50–100 m) [ Keller , ; Hodell and Vayavananda , ; Nathan and Leckie , ; Pearson and Wade , ] and calcification at greater depth (thermocline or subthermocline) by D. venezuelana (100–250 m) [e.g., Gasperi and Kennett , ; Hodell and Vayavananda , ; Nathan and Leckie , ; Matsui et al , ] throughout the early to middle Miocene. We therefore estimated the vertical thermal gradient in the EEP by subtracting the δ 18 O values of P. siakensis from those of D. venezuelana (Figure ).…”
Section: Discussionmentioning
confidence: 93%
“…• Table S1 Correspondence to: H. Matsui Matsui et al, 2016], and measurements at several sites have elucidated zonal (east to west) and meridional (pole to equator) temperature gradients [e.g., Fedorov et al, 2015]. Thermocline history (vertical and zonal gradients) in the equatorial Pacific can thus be reconstructed from analyses of foraminiferal tests.…”
Section: 1002/2016pa003058mentioning
confidence: 99%
See 1 more Smart Citation